2003
DOI: 10.1026//0933-6885.14.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Musikalische und mimische Emotionserkennung: Eine Pilotstudie mit psychiatrischen Patienten

Abstract: Zusammenfassung. Dargestellt wird eine kontrollierte explorative Pilotstudie mit acht Patienten einer psychiatrischen Tagesklinik zur Erkennung von grundlegenden Gefühlsqualitäten (u.a. Freude, Trauer, Ärger) in Mimik und Musik 1 Wir danken dem Psychiatrischen Zentrum Nordbaden (PZN) für die Unterstützung bei der Durchführung dieser Pilotstudie. . Die Studie untersucht, ob sich Unterschiede in der Erkennungsleistung zwischen mimisch und musikalisch dargestellten Emotionen ergeben und ob die Emotionserkennung z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In order to explore the possibility of basic emotions being recognized in acoustic stimuli unknown to the participants, the German Centre of Music Therapy Research developed a test of emotion perception in music (Busch et al, 2003). A pilot study demonstrated that 18 musical segments representing six emotions (happiness, anger, disgust, surprise, sadness, and fear) could be reliably allocated to the intended emotional categories.…”
Section: Rationale Of the Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to explore the possibility of basic emotions being recognized in acoustic stimuli unknown to the participants, the German Centre of Music Therapy Research developed a test of emotion perception in music (Busch et al, 2003). A pilot study demonstrated that 18 musical segments representing six emotions (happiness, anger, disgust, surprise, sadness, and fear) could be reliably allocated to the intended emotional categories.…”
Section: Rationale Of the Present Studymentioning
confidence: 99%
“…The current trial investigated the same musical items that were used in our previous studies (Busch et al, 2003;Mohn et al, 2011). Professional musicians were instructed to improvise short musical pieces on instruments of their choice in a way that a listener should be able to decode one of the intended basic emotions (happiness, anger, disgust, surprise, sadness, and fear).…”
Section: Test Of Emotion Perception In Musicmentioning
confidence: 99%